Implementasi Active Directory Singgle Domain pada Anak Perusahan Akita Jaya Mobilindo Jakarta - Ahmad Rais Ruli (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2017)
In globalization of technology, it’s easy and faster to process the data. One of data processing that allows and makes easy the administrator on the processing of access rights is Active Directory. Users can be controlled on the access rights of data application with the implementation of Active Directory. The administrator can give the access rights of local data application and local exchange access. Akita Jaya Mobilindo is an automotive company where the subsidiaries locate in JABODETABEK area. This reason, the processing data of this corporate uses the centralize of data where it can be accessed by user in all the corporate branches, therefore, implementation of single domain is the right choosen as a solution that is faced by administrator. Active directory makes easier on the controlling and managing of data access that it will be provided to the users.